(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article explores pedagogical opportunities for cultivating reflective abilities in future teachers, emphasizing their critical role in professional development and effective teaching practice. Reflective abilities enable educators to analyze their experiences, adapt teaching strategies, and foster student-centered learning environments. The study examines various pedagogical approaches, such as reflective journals, peer observation, case-based discussions, and mentorship programs, to develop these skills in pre-service teacher education. By integrating theoretical frameworks and practical applications, the article highlights how structured reflection enhances self-awareness, decision-making, and resilience in teaching. The findings suggest that intentional, scaffolded reflective practices in teacher training programs can significantly prepare future educators for dynamic classroom challenges.